Characterization of human immunodeficiency virus type 1 Pr55gag membrane association in a cell-free system: requirement for a C-terminal domain. - Platt, E J (1994)
Association of the human immunodeficiency virus type 1 (HIV-1) gag polyprotein precursor with cellular membranes is necessary for assembly of virions. We used in vitro synthesized HIV-1 gag to study its association with isolated cellular membranes. Rabbit reticulocyte lysates programmed with HIV-1 gag mRNA incorporated [35S]methionine and [3H]myristate into two predominant species of 55 kDa and 40 kDa. Radioimmunoprecipitation with HIV-1-specific antibodies suggested that the 55-kDa protein represented the polyprotein precursor (Pr55gag), while the 40-kDa protein was a mixture of N- or C-terminal truncations of the gag precursor. The Pr55gag protein bound to cellular membranes, while the 40-kDa mixed protein species did not. Membrane binding studies with C terminus-truncated and point mutants revealed that the seven-amino acid sequence located between the two Cys-His arrays in the nucleocapsid region was necessary for stable association to occur. Therefore, we propose that signals in addition to myristate are required for the membrane association of HIV-1 gag proteins and that these signals include a domain in the nucleocapsid protein.